Evading the Entrepreneurship: A Study to Discover Implementable Online Approaches to Avoid Greenhouse Consequences - Feng, Lian; Wenting, Hu; Akhter, Tazeem; Albasher, Gadah; Aamir, Alamzeb; Imran, Asma (Frontiers in Psychology, 2021)
Greenhouse gases emissions due to climate change are a continuous threat to the global world, mainly relying on numerous products' pervasive consumption including synthetic and non-synthetic products. This research focused on students' green purchase intentions in Pakistan towards different products which are related to minimising the greenhouse effect and available for sale on numerous e-commerce websites, ultimately proceeding to green entrepreneurship. This study's main objective was to determine that which methodology was better among product listing, social media advertising and online virtual community to enhance customer online green purchase intention while considering online information about the greenhouse effect as a mediating variable. The AMOS 24 was used for this research. SEM was performed with the help of bootstrap methodology. The research was conducted on 280 students at different educational institutes in Pakistan using a simple random sampling technique. A finding of this study suggested that all three methods positively impacted the green purchase intention of consumers and green entrepreneurship but online virtual communities could be considered in a more effective way to enhance the green purchase intention of its targeted customers.